EDUKASI MANFAAT MINUM SUSU BAGI SISWA- SISWI SDN 3 MARGO DADI PROVINSI LAMPUNG - Ardyani Sonjaya, Niken; Wahyudin, Gaeldeba; Arum Nabila, Anisa; Dwi Satria, Dewantara; Adestha, Agung; Hasani, Rahmat (Jurnal Media Pengabdian Kepada Masyarakat, 2023)
Currently, there are still many people who do not care about what they eat and drink, both adults and children. The problem faced by the Indonesian people is the low awareness of meeting nutritional needs, one of which is consuming milk. Milk is a source of animal nutrition that contains protein, nutrients and enormous benefits for health. This happens due to a lack of knowledge about how to recognize safe snacks, food, including drinks. The importance of knowledge about drinking milk is still not fully distributed in society, especially among children at SDN 3 Margo Dadi, Jati Agung District, South Lampung Regency. Socialization of the benefits of drinking milk is carried out to increase children's awareness of increasing milk consumption. This activity is carried out in stages, namely 1). field observation 2). counseling, and 3). UHT milk drinking demonstration and will be held on Thursday 23 October 2023 at 13.00 WIB until finished. The benefit of this activity is that it provides students with knowledge about the importance of consuming milk every day. Students prefer the chocolate flavored variant of UHT milk because the sweet taste is really liked by children.